2020
DOI: 10.3233/jad-200088
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Effects of Treating Obstructive Sleep Apnea: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Obstructive sleep apnea (OSA) is associated with cognitive impairment and increased risks of dementia. However, the effect of continuous positive airway pressure (CPAP) on cognitive function in patients with OSA is still controversial. Objective: To evaluate the cognitive effects of CPAP treatment on OSA. Methods: We systematically searched PubMed, EMBASE, and Cochrane Library for randomized controlled trials (RCT) in the corresponding fields. Results: Totally 14 studies and 1,926 participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Continuous positive airway pressure (CPAP) is the current standard of treatment of obstructive sleep apnoea (OSA), since its description in the early 1980s [1], and is highly effective in suppressing respiratory disturbances during sleep as well as improving several patient clinical manifestations [2][3][4][5][6][7][8]. However, advances in the pathophysiological understanding of OSA have shown that not only anatomical narrowing of the upper airways, but also impairment of muscle responsiveness, arousability and respiratory drive all contribute to the pharyngeal collapse that is the hallmark of the disorder [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Continuous positive airway pressure (CPAP) is the current standard of treatment of obstructive sleep apnoea (OSA), since its description in the early 1980s [1], and is highly effective in suppressing respiratory disturbances during sleep as well as improving several patient clinical manifestations [2][3][4][5][6][7][8]. However, advances in the pathophysiological understanding of OSA have shown that not only anatomical narrowing of the upper airways, but also impairment of muscle responsiveness, arousability and respiratory drive all contribute to the pharyngeal collapse that is the hallmark of the disorder [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a meta-analysis based on 1926 subjects, M.L. reported that CPAP treatment (average treatment length: 6 weeks) had a (borderline) significant effect on attention and information processing speed in subjects with severe OSA, with no effects being identified for attention and speed of information processing, executive function, or memory [9]. After the onset of MCI, Richards et al found that subjects with MCI and mild OSA showed improved psychomotor/cognitive processing speed after 1 year of CPAP treatment [35,36].…”
Section: Sleep Apnoea and Cognitionmentioning
confidence: 99%
“…Indeed, all but M.L. and Y. Wang (2020) reported a significant decrease in daytime sleepiness after treatment [8,9,33,34,36], although Bhat et al (2018) did not find changes in sleepiness to be predictive of improved vigilance [33]. However, older studies based on limited data have found that cognitive function did not improve after CPAP in subjects who did not experience subjective daytime sleepiness, irrespective of OSA severity [9,37].…”
Section: Wais-iv Wechslermentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous positive airway pressure (CPAP) has become the current gold standard of OSA treatment since the early 1980s [2]. CPAP has been proven to be highly effective in decreasing respiratory events during sleep and in improving the clinical manifestations of the disease [3][4][5]. However, almost 50% of the patients who are prescribed CPAP are not adherent to it at all or use it <4 h per night [6].…”
mentioning
confidence: 99%